Analysis Of The Preparation Of Micro, Small, and Medium Enterprise Financial Statements Based On Sak EMKM (Case Study of Saung Alam Raya Cafe, Tanah Jawa District, Simalungun Regency) - Mayliza Putri; Tarigan, Wico Jontarudi; Purba, Djahotman (Jurnal Ilmiah Accusi, 2024)
This research aims to determine the application of preparing financial reports for Saung Alam Raya Cafe Micro, Small and Medium Enterprises (MSMEs) based on SAK EMKM and explain the obstacles faced in its implementation. This research is descriptive qualitative research using a case study approach. Data collection was carried out through interviews. The research results show that the financial reports prepared are still not in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM). Then, the information in the financial reports is still simple and still uses cash in and cash out calculations. The obstacles experienced by owners in preparing financial reports are the owner's lack of understanding of financial reports and lack of time allocation